Resolution of High-Frequency Mesoscale Intracortical Maps Using the Genetically Encoded Glutamate Sensor iGluSnFR - Yicheng Xie; Allen W. Chan; Alexander McGirr; Songchao Xue; Dongsheng Xiao; Hongkui Zeng; Timothy H. Murphy (2016)
Wide-field-of-view mesoscopic cortical imaging with genetically encoded sensors enables decoding of regional activity and connectivity in anesthetized and behaving mice; however, the kinetics of most genetically encoded sensors can be suboptimal for in vivo characterization of frequency bands higher than 1-3 Hz. Furthermore, existing sensors, in particular those that measure calcium (genetically encoded calcium indicators; GECIs), largely monitor suprathreshold activity. Using a genetically encoded sensor of extracellular glutamate and in vivo mesoscopic imaging, we demonstrate rapid kinetics of virally transduced or transgenically expressed glutamate-sensing fluorescent reporter iGluSnFR. In both awake and anesthetized mice, we imaged an 8 × 8 mm field of view through an intact transparent skull preparation. iGluSnFR revealed cortical representation of sensory stimuli with rapid kinetics that were also reflected in correlation maps of spontaneous cortical activities at frequencies up to the alpha band (8-12 Hz). iGluSnFR resolved temporal features of sensory processing such as an intracortical reverberation during the processing of visual stimuli. The kinetics of iGluSnFR for reporting regional cortical signals were more rapid than those for Emx-GCaMP3 and GCaMP6s and comparable to the temporal responses seen with RH1692 voltage sensitive dye (VSD), with similar signal amplitude. Regional cortical connectivity detected by iGluSnFR in spontaneous brain activity identified functional circuits consistent with maps generated from GCaMP3 mice, GCaMP6s mice, or VSD sensors. Viral and transgenic iGluSnFR tools have potential utility in normal physiology, as well as neurologic and psychiatric pathologies in which abnormalities in glutamatergic signaling are implicated.We have characterized the usage of virally transduced or transgenically expressed extracellular glutamate sensor iGluSnFR to perform wide-field-of-view mesoscopic imaging of cortex in both anesthetized and awake mice. Probes for neurotransmitter concentration enable monitoring of brain activity and provide a more direct measure of regional functional activity that is less dependent on nonlinearities associated with voltage-gated ion channels. We demonstrate functional maps of extracellular glutamate concentration and that this sensor has rapid kinetics that enable reporting high-frequency signaling. This imaging strategy has utility in normal physiology and pathologies in which altered glutamatergic signaling is observed. Moreover, we provide comparisons between iGluSnFR and genetically encoded calcium indicators and voltage-sensitive dyes.